PELAKSANAAN PEMBELAJARAN BOLA VOLI DALAM KEHIDUPAN NEW NORMAL PADA SISWA KELAS IV SD NEGERI BELLE KABUPATEN TIMOR TENGAH SELATAN - Tabun, Risto; Kerihi, Simson Robinson; Atty, Jimmy (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2021)
The implementation of volleyball learning in the new normal life for fourth grade students of SD Negeri Belle II, Timor Tengah Selatan Regency is carried out in accordance with the objectives of learning volleyball. But in its implementation the infrastructure is less than optimal so it must be modified by the teacher. The purpose of this study was to determine the implementation of volleyball learning in the new normal life at Belle II Elementary School, South Central Timor Regency. This study uses a qualitative descriptive approach. The subjects of this study were the fourth grade students of SD Negeri Belle II, Timor Tengah Selatan Regency, totaling 33 people and physical education teachers. Data collection techniques by observation, interviews, and documentation. The data analysis technique used descriptive qualitative analysis with data reduction steps, data display, and conclusion drawing (verification). The results showed that the learning of volleyball in the fourth grade students of SD Negeri Belle II, Timor Tengah Selatan Regency took place in accordance with the objectives of learning volleyball. But in practice the infrastructure is less than optimal so the teacher tries to modify the tool.